Rising Income Inequalities – the Causes of and Consequences for Long-term Growth - Sordyl, Marta (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2019)
Objective: The objective of the paper is to identify the channels through which income inequalities affect the short-term economic situation and long-term growth. Research Design & Methods: As initial research, the analysis is based on a literature review. Over the course of the review, this hypothesis was verified: inequalities have a negative impact on GDP growth rates and economic stability. Findings: The paper explains mechanisms through which inequalities affect aggregate demand, output and accumulation, accentuating immanent threats of income disparities, such as rising debt burdens (both private and public) and current-account imbalances. Implications / Recommendations: A policy alternative is proposed in the form of a wage-led growth strategy. This will strengthen the position of workers in the economy and thus allow the wage share to grow at least apace with productivity gains. Contribution: The concept of wage-led growth is rarely discussed in the mainstream literature and deserves more attention.